Performance of WDM-OFDM for Using Unequalized Optical Frequency Comb - Villarreal, Gabriel; Cardenas, Ana M.; Botia, Javier (Revista IEEE América Latina, 2015)
Optical Frequency Comb Generation (OFCG) technique using a Mach Zehnder modulator (MZM) allows to diminish cost of an optical access network based on Wavelength Division Multiplexing (WDM), because it just needs a single source for generating several optical carriers. However, the unequalized comb power is a limitation for the performance of the network. In order to maintain its simplicity and low cost, we propose to combine WDM with Orthogonal Frequency Division Multiplexing (OFDM). This solution allows changing the number of bits per carrier, being adaptive to several link impairments. An algorithm based on bit‒loading strategies maximizes the transmission rate and mitigates the effects of the unequalized channels on a WDM network. The simulation results show the efficiency of the adaptive algorithm to increase the channel capacity up to 35 Gbps over 5 unequalized WDM channels.